Perceptions and Performance of dental students using Conventional and Virtual Microscopy in Oral Pathology - Gulmina Saeed Orakzai; Waqar-Un-Nisa; Saima Irshad; Nabeela Naeem; Ammarah Afreen; Zarah Afreen (Journal of Rawalpindi Medical College, 2023)
Virtual microscopy for showing histopathological slides have been in use for quite some time. This method of teaching is considered to be a good replacement for conventional microscopy using glass slides. This study was carried out to analyze the perception and performance of dental students regarding the use of conventional microscopic slides and virtual slides in relation to teaching and learning. Material and methods: Eighty undergraduate dental students who had studies the subject of oral pathology as a compulsory subject at Watim Dental college were invited to participate in the study. Students not willing to take part in the study were excluded. The questionnaires were duly filled and test was taken by the students using either virtual slides or glass slides. The data was collected and analyzed using SPSS 20. Results: A total of eighty undergraduate students participated in the study. The results showed that dental students had a higher acceptance rate (all P-value<0.001) for cases taught via virtual microscopy and they out performed in cases shown on virtual slides (p<0.01). Conclusion: In this study the students preferred teaching of oral histopathology via virtual slides over conventional glass slides and it also contributed more to their learning. Keyword: Conventional microscopy, dental students, virtual microscopy, oral pathology